2021
DOI: 10.9778/cmajo.20200244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hospitalized patients with COVID-19 who did and did not live in residential care facilities in Montréal: a retrospective case series

Abstract: Q uebec was the epicentre of the COVID-19 health crisis in Canada between March and August 2020, accounting for more than half of Canada's cases and deaths. 1 As of Feb. 9, 2021, over 271 700 cases and 10 000 deaths attributed to COVID-19 occurred in Quebec, of which more than 50% of cases and 60% of deaths occurred in Montréal. 1 The first case of COVID-19 in Quebec was diagnosed on Feb. 27, 2020, in an international traveller. 2 Early transmission dynamics were driven by returning international travellers, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The result of a previous study demonstrated multiple comorbidities and underlying conditions have been associated with severe illness 10,11 . So, although severe disease can occur in any individual, most with severe disease have at least one risk factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of a previous study demonstrated multiple comorbidities and underlying conditions have been associated with severe illness 10,11 . So, although severe disease can occur in any individual, most with severe disease have at least one risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…The result of a previous study demonstrated multiple comorbidities and underlying conditions have been associated with severe illness. 10 , 11 So, although severe disease can occur in any individual, most with severe disease have at least one risk factor. In the study of Onder et al 12 in Italy the mean number of pre‐existing comorbidities was about three inpatients who died from COVID‐19.…”
Section: Discussionmentioning
confidence: 99%
“…By mid-April 2020, COVID-19 swept through public and private RCFs in Quebec with numerous outbreaks [ 30 ]. By the end of the first wave (July 2020), residents of RCFs accounted for 22% of all cases, 28% of hospitalizations, and 79% of COVID-attributed mortality [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…By mid-April 2020, COVID-19 swept through public and private RCFs in Quebec with numerous outbreaks [30]. By the end of the first wave (July 2020), residents of RCFs accounted for 22% of all cases, 28% of hospitalizations, and 79% of COVID-attributed mortality [30,31]. Widespread transmission was facilitated by chronic structural deficiencies in these institutions including crowding, communal spaces, low staff-to-resident ratios, reliance on a precariously employed workforce who worked in several facilities to earn a living wage (most with no sick pay) so they could not afford to take time off work, and lack of adequate PPE [32][33][34][35].…”
Section: Plos Onementioning
confidence: 99%